Estratégias comunicativas das marcas Vivo E Tim na publicidade impressa - Fernandes, Renata Sertório (2006)
This master degree main objective searched to evaluate the communication strategies of the marks of the companies of mobile telecommunication Tim and Vivo through theirs main manifestations, being considered as being exactly: names, logotypes, logomarks and slogans, these in turn, presented in the media printed. The objects of the analysis are announcements published in media printed, divulged in the two main ones reviewed weekly Brazilians: Veja e Época. Two of them, institutional advertisings (one of each company) are studied at great length, excessively they will be briefly analyzed. The mark and its manifestations are constituted by complex processes of meaning and directly are related to the language and the communication between company and consumers. The semiotics offers ways to investigate the existing potential of communication in the elements that constitute the representation of the mark, as well as its presentation through the different manifestations of marketing. The intention is to investigate the effect of the potential generated by the announcement advertising executive in general, and mainly for the mark through its main manifestations, in more specific way. From there, we ask: what strategies the companies promote to create and to keep this image to the consumers, by means of communications contracts established in the relation between sender and receiver